Potential use of Dry Metallic Copper and Colloidal silver solution to reduce survival of Pseudomonas aeruginosa isolates from healthcare environment - Hadi, Alyaa; Melconian, Alice (Iraqi Journal of Science, 2024)
The objective of this study was to evaluate the activity of dry metallic copper and colloidal silver solution to reduce the viability of P.aeruginosa isolates compared with stainless steel as a control. Three clinical isolates of P.aeruginosa (108, 110 and 111 ) which were multi antibiotics resistant tested by inoculating 107 CFU/ml on to coupons( 1cm x 1cm) of copper and stainless steel and incubated at room temperature for various time periods ranging from 30minutes up to 180 minutes .Bacterial viability was determined by plate viable count CFU/ml. The results on copper coupons shows complete killing of isolates after 120 min in contrast to stainless steel, viable organisms were detected after 180 min, indicating a significant P value (P >0.0001) . To the evaluation of colloidal silver activity on P.aeruginosa isolates, 107 CFU/ml of the resistant bacterial isolates were tested against 5ppm and 10 ppm of colloidal silver solution at room temperature for various time periods ranging from 30min up to 180 min also by using agar dilution method and killing rate technique .The results shows that bacterial isolates were sensitive to colloidal silver in both concentrations and complete killing of microorganisms achieved using 10 ppm concentration after 180 min with a significant P value (P >0.0001) .